2018
DOI: 10.1016/j.apsb.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-derived biomimetic nanoparticulate drug delivery systems for cancer therapy

Abstract: Precise drug delivery to tumors with low system toxicity is one of the most important and challenging tasks for pharmaceutical researchers. Despite progress in the field of nanotherapeutics, the use of artificially synthesized nanocarriers still faces several challenges, including rapid clearance from blood circulation and limited capability of overcoming multiple physiological barriers, which hamper the clinical application of nanoparticle-based therapies. Since leukocytes (including monocytes/macrophages, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 67 publications
(101 reference statements)
0
75
0
3
Order By: Relevance
“…Although water-soluble polymers, cationic lipids, or liposome nanocarriers are less toxic than a viral vector, the delivery efficiency remains lower [171]. Since leukocytes (including monocytes/macrophages, neutrophils, dendritic cells, and lymphocytes) or MSCs target tumors and can migrate across physiological barriers like the BBB, these cell types are increasingly utilized as carriers to transfer NPs to tumors [172]. As leukocytes/ MSCs follow the same pattern of migration as tumor cells to cross the BBB, these cellular mechanisms can be utilized effectively to deliver miRNA conjugated NPs to the BMs.…”
Section: Mirna and Bcbm Therapeuticsmentioning
confidence: 99%
“…Although water-soluble polymers, cationic lipids, or liposome nanocarriers are less toxic than a viral vector, the delivery efficiency remains lower [171]. Since leukocytes (including monocytes/macrophages, neutrophils, dendritic cells, and lymphocytes) or MSCs target tumors and can migrate across physiological barriers like the BBB, these cell types are increasingly utilized as carriers to transfer NPs to tumors [172]. As leukocytes/ MSCs follow the same pattern of migration as tumor cells to cross the BBB, these cellular mechanisms can be utilized effectively to deliver miRNA conjugated NPs to the BMs.…”
Section: Mirna and Bcbm Therapeuticsmentioning
confidence: 99%
“…These DDVs utilize cell membrane lipids, proteins, and sugars to impart stealth or specific cell properties (e.g., leukocyte). It was shown that leukocyte mimetic vehicles effectively targeted sites of inflammation caused by disease or cancer . Red blood cell membranes were used to cloak encapsulated drug and increase circulation time .…”
Section: Ddv Selectionmentioning
confidence: 99%
“…A suitable strategy for leukocyte-derived drug delivery is to take advantage of the biocompatibility and biological function of living leukocytes to prolong the life of drugs in vivo and to target inflammatory tissue with leukocytes for site-specific drug delivery (Huang et al., 2018 ). The loading cargoes by leukocytes are also well-investigated and summarized, mainly including membrane bonding and encapsulation.…”
Section: Cells Used For Cell-mediated Drug Deliverymentioning
confidence: 99%